Edvard Munch, 1863-1944 - Bischoff, Ulrich; Munch, Edvard, 1863-1944. (Los Angeles : Taschen, 2000)
An introduction to the life and work of nineteenth-century Norwegian painter Edvard Munch, discussing his cultural and historical importance, and including a chronology and over one hundred color illustrations with explanatory captions.
Cover title: Munch.
Translated from the German.
Adult
Keywords: Munch, Edvard, -- 1863-1944 -- Criticism and interpretation; Munch, Edvard, -- 1863-1944 -- Criticism; Expressionism (Art) -- Norway; Expressionism (Art) -- Norway